Effect of Gamma Irradiation on Structural and Biological Properties of a PLGA-PEG-Hydroxyapatite Composite - Sima Shahabi; Farhood Najafi; Abbas Majdabadi; Tabassom Hooshmand; Masoumeh Haghbin Nazarpak; Batool Karimi; Seyyed Mostafa Fatemi (The Scientific World Journal)
Gamma irradiation is able to affect various structural and biological properties of biomaterials In this study, a composite of Hap/PLGA-PEG and their ingredients were submitted to gamma irradiation doses of 25 and 50 KGy. Various properties such as molecular weight (GPC), thermal behavior (DSC), wettability (contact angle), cell viability (MTT assay), and alkaline phosphatase activity were studied for the composites and each of their ingredients. The results showed a decrease in molecular weight of copolymer with no change in the glass transition and melting temperatures after gamma irradiation. In general gamma irradiation can increase the activation energy ΔH of the composites and their ingredients. While gamma irradiation had no effect on the wettability of copolymer samples, there was a significant decrease in contact angle of hydroxyapatite and composites with increase in gamma irradiation dose. This study showed an increase in biocompatibility of hydroxyapatite with gamma irradiation with no significant effect on cell viability in copolymer and composite samples. In spite of the fact that no change occurred in alkaline phosphatase activity of composite samples, results indicated a decrease in alkaline phosphatase activity in irradiated hydroxyapatites. These effects on the properties of PLGA-PEG-hydroxyapatite can enhance the composite application as a biomaterial.